A review on the research progress and future development of nano‐modified cellulose insulation paper. Issue 2 (21st December 2021) - Tang, Chao; Chen, Rui; Zhang, Jinzhu; Peng, Xiao; Chen, Binghao; Zhang, Liusheng
Abstract: Focussing on the insulating material of power transformer—cellulose insulation paper, this paper first introduces the basic characteristics and engineering application background of insulation paper. Then, the research progress of improving the mechanical properties, thermal stability and electrical properties of insulation paper by nano modification in recent years is compared, and the promotion mechanism is analysed. In addition, in practical engineering application, the oil–paper composite insulation system composed of insulation paper and insulating oil is used for the internal insulation of oil immersed transformer. Therefore, the influence of modified insulation paper on the performance of oil–paper composite insulation system is analysed. Finally, the newly reported new insulation paper is introduced, and the future development trend of modification of traditional insulation paper is analysed.